Pengaruh Pemberian Edukasi Pencegahan Stunting dengan Pedoman Isi Piringku Terhadap Pengetahuan Ibu Hamil - Nissa Nur Maulidiah; Qomariyah Qomariyah; Desi Soraya (Inovasi Kesehatan Global, 2025)
A continuous lack of nutritional intake causes stunting, a condition of malnutrition that leads to growth disorders in infants. Providing pregnant women with balanced nutrition education is one of the preventive measures against stunting. Objective: The research determined the effect of providing education on stunting prevention using the "Meals on My Plate" guidelines at the Mijen public health care. Method: This quantitative method research applied a quasi-experimental with a one-group pretest-posttest design. The sampling technique was accidental sampling. The researchers analyzed both univariate and bivariate data using the Shapiro-Wilk normality test and the Wilcoxon test. Results: the Wilcoxon test obtained a value of 0.000 < 0.05. The result accepts Ha and denies Ho, indicating a significant effect of providing education on stunting prevention using the "Meals on My Plate" guidelines, which has the potential to influence the knowledge level of pregnant women at the Mijen Public Health Care in Semarang by 5.859 times.